Comparison of Chronic Hemodialysis Patients under Strict Volume Control with respect to Cardiovascular Disease - Dursun, Fadime Ersoy; Gunal, Ali Ihsan; Kirciman, Ercan; Karaca, Ilgin; Dagli, Mustafa Necati (Hindawi Ltd, 2019)
Background. The objective of this study was to determine the effects of strict volume control and nondipper situation on cardiovascular disease in chronic hemodialysis patients. Methods. This study is an observational and cross-sectional study including 62 patients with normotensive chronic hemodialysis using no antihypertensive drugs. A series of measurements including ambulatory blood pressure monitoring, left ventricular mass index by echocardiography, common carotid artery intima-media thickness by ultrasound, and body fluids by bioimpedance analysis were conducted for all subjects. Results. The patients were divided into two groups as dippers and nondippers according to their ambulatory blood pressure monitoring results. Average 48 h systolic, diastolic, and mean arterial blood pressure and nocturnal systolic, diastolic, and mean arterial blood pressure were significantly different between the dipper and nondipper groups (p<0.05). Before and after dialysis, extracellular fluid/intracellular fluid and extracellular fluid/dry body weight ratios were significantly higher in the nondipper group. Left ventricle mass index and interventricular septum thickness were significantly higher in the nondipper group (p<0.05). Left ventricle ejection fraction was significantly lower and common carotid artery intima-media thickness was higher in the nondipper group with a statistical significance (p<0.05). A two-predictor logistic model was fitted to the data to predict the comparability of dippers and nondippers. Conclusion. According to logistic regression analysis, the odds ratio for daytime diastolic blood pressure indicates that nondippers are 0.45 times more likely to have high blood pressure than dippers in daytime. But in night time, nondippers are about 2.55 times more likely to have high blood pressure comparing to dippers. An important finding of this study is that nondipping pattern is associated with cardiac hypertrophy and lower left ventricle ejection fraction in dialysis of patients with no hypertension. The results also suggest that applying strict volume control to achieve a normal blood pressure alone is not sufficient to reduce the risk of cardiovascular morbidity and mortality if the patients do not have a dipper status of nocturnal blood pressure.
Keywords: Ambulatory Blood-Pressure; Risk-Factors; Fluid Management; Body-Composition; Hypertension; Hyperhomocysteinemia; Inflammation; Variability; Mortality; Health